Surrogacy of one-year survival for overall survival in advanced hepatocellular carcinoma - Yuzhi Jin; Hui Ren; Qianhua Yue; Wei Wu; Chuan Liu; Yixuan Guo; Peng Zhao (BMC Cancer, 2024)
Abstract Background The increasing number of sequential treatments complicates the evaluation of overall survival (OS) in clinical trials for hepatocellular carcinoma (HCC), therefore, reliable surrogate endpoints (SEs) are required. This study aimed to evaluate the surrogacy of progression-free survival (PFS) and one-year (1-yr) milestone survival for OS in HCC trials. Methods We systematically searched databases for randomized clinical trials that evaluated systemic treatments for advanced HCC. Individual patient data were reconstructed to calculate the 1-yr survival rate. We adopted a two-stage meta-analytic validation model to evaluate the correlation between SEs and OS, and the correlation between treatment effects on SEs and OS. The hazard ratio (HR) was calculated to assess the treatment effects on PFS and OS, and the 1-yr survival ratio was calculated to evaluate the treatment effects on the 1-yr milestone survival. Results Thirty-two HCC trials involving 13,808 patients were included. A weak correlation was detected between the median PFS and median OS (R2 = 0.32), whereas the correlation improved between PFS HR and OS HR (R2 = 0.58). We identified strong correlations between the 1-yr survival rate and median OS and between the 1-yr survival ratio and OS HR (R2 = 0.74 and 0.65, respectively). In subgroup analyses, PFS HR strongly correlated with OS HR in trials relevant to immune checkpoint inhibitors (ICIs). Although the correlation remained weak between PFS and OS even in trials with PFS HR ≤ 0.6, the 1-yr survival rate and 1-yr survival ratio were strong surrogates for median OS and OS HR, respectively (R2 = 0.77 and 0.75). Conclusions One-year milestone survival outperformed PFS as a SE for OS in HCC, indicating the application of 1-yr survival as a secondary endpoint. In particular, PFS HR was a potential SE for OS HR in the ICI trials.